Providing solutions to solve the challenges of comprehensive development of information technology (IT) in health service organizations of Iran (case study: Social Security Organization) (Scientific Journal of Research Studies in Future Management, 2025)
In recent decades, IT-based technologies have played a significant role in enhancing the efficiency and quality of healthcare services. However, the development of these technologies within Iran's healthcare organizations faces numerous challenges.The results indicated that technical and security challenges remain significant barriers to IT advancement that require further attention. In conclusion, the findings from this research suggest that for improving the widespread development of IT in Iran's healthcare organizations, integrated approaches including training, investment in infrastructure, and strengthening interdepartmental communications must be implemented comprehensively and cohesively. These results can assist policymakers and managers in healthcare organizations to more effectively tailor their programs for the development of innovative technologies.